Analisis Sensitivitas dan Optimisasi Sistem Pencahayaan Elektrik pada Gedung Olahraga Bulu Tangkis - Rizki A. Mangkuto; Faizatuzzahrah Rahmaniah; Tasya Nadya H.; Diana Pinasthika (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
Electric lighting in indoor sport halls is essential for providing sufficient amount of light required for the sport activities, while maintaining visual comfort for the occupants. To do so, design optimization of the lighting system is often necessary. This study provides an example of design optimization for electric lighting system in the case of an indoor badminton hall in Bandung, according to the standard of EN 12193. The electric lighting system in the hall was modelled and simulated in DIALux evo simulation tool, validated with the measured values in the existing situation. One-at-a-time sensitivity analysis was then performed to investigate the influence of building parameters and luminaire configuration on the lighting performance and visual comfort parameters. Optimization process was realized by changing the dominant input parameters so that the required output parameters are achieved. Based on simulation results, the optimum luminaires are those of fluorescent tubes with luminous flux of 3,244 lm and electric power of 58 W per unit, mounted 5 m high above the floor. The optimum ceiling and floor reflectance are respectively 0.80 and 0.80. Based on optimization of those input parameters, the average illuminance on the field can be increased to 336~364 lx, the uniformity can be increased to 0.84~0.89, and the UGR glare index can be reduced to 19, satisfying the standard of EN 12193.